Force transmission at the handle - Kleshnev, V. (BioRow, 2022)
Newly data obtained with the BioRow 4D handle allows for better understanding of Rowing Biomechanics, fine analysis of individual rowing technique and rigging specifics (say, effect of span/spread, oar pitch, etc.).